Fluid New York : cosmopolitan urbanism and the green imagination - Joseph, May (Duke University Press, 2013)
Fluid New York offers reflections on how New York began to incorporate the city's archipelago ecology into plans for a livable and sustainable future in the decade between September 11 and Hurricane Sandy.